2019
DOI: 10.1002/anie.201902413
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of Materials with Catalytic Effects in Li–S Batteries: Enhanced Redox Kinetics

Abstract: Lithium–sulfur batteries (LSBs) are cost‐effective and high‐energy‐density batteries. However, the insulating nature of active materials, the shuttle effect, and slow redox kinetics lead to severe capacity decay and low rate capabilities. Numerous multimodal approaches have been attempted to tackle these issues and have pushed the cycle stability and energy density to higher levels. Recently, accelerating the redox kinetics using catalytic materials has been considered as a means to realize high‐performance LS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
270
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 424 publications
(289 citation statements)
references
References 99 publications
(88 reference statements)
2
270
0
Order By: Relevance
“…Atomic‐scale electrocatalysts in Li–S batteries are strongly considered to enhance redox kinetics of sulfur conversion, as the atomically dispersed active sites on substrates can maximize the atom‐utilization efficiency for sulfur species modulation and curtail inert dosage in electrodes . Single cobalt and iron atoms coordinated with nitrogen have been explored as electrocatalysts to enhance kinetic conversion from LiPSs to Li 2 S and mitigate LiPS shuttle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atomic‐scale electrocatalysts in Li–S batteries are strongly considered to enhance redox kinetics of sulfur conversion, as the atomically dispersed active sites on substrates can maximize the atom‐utilization efficiency for sulfur species modulation and curtail inert dosage in electrodes . Single cobalt and iron atoms coordinated with nitrogen have been explored as electrocatalysts to enhance kinetic conversion from LiPSs to Li 2 S and mitigate LiPS shuttle.…”
Section: Introductionmentioning
confidence: 99%
“…Atomic-scale electrocatalysts in Li-S batteries are strongly considered to enhance redox kinetics of sulfur conversion, as the atomically dispersed active sites on substrates can maximize the atom-utilization efficiency for sulfur species modulation and curtail inert dosage in electrodes. 47 Single cobalt [48][49][50][51] and iron 52,53 atoms coordinated with nitrogen have been explored as electrocatalysts to enhance kinetic conversion from LiPSs to Li 2 S and mitigate LiPS shuttle. However, kinetic understanding of the electrocatalytic capabilities of atomic electrocatalysts for Li-S batteries is rather limited, yet critically important to rational design of high-efficiency electrocatalysts in Li-S batteries.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, transition metal nitride (e.g., TiN, VN, and MoN) have been used as anchoring materials because of the high conductivity and strong chemical adsorption for polysulfides . However, polysulfides transformation and Li 2 S precipitation behaviors were not investigated in these works, which is of great significance for enhancing the utilization of sulfur and improving the energy density of the batteries . Yang et al demonstrated that the TiO 2 ‐TiN heterostructures loaded on the separator possess favorable electrocatalysis ability to accelerate polysulfides transformation .…”
mentioning
confidence: 99%
“…Lithium–sulfur battery, typically composed of a lithium metal anode and sulfur cathode, is an attractive candidate to replace lithium‐ion battery for its high theoretical capacity (sulfur: 1672 mAh g −1 , lithium metal: 3860 mAh g −1 ), natural abundance, low cost and safety. [ 121 ]…”
Section: Application In Advanced Battery Systemsmentioning
confidence: 99%